2019
DOI: 10.1080/15548627.2019.1628541
|View full text |Cite
|
Sign up to set email alerts
|

Loss of autophagy in chondrocytes causes severe growth retardation

Abstract: Chondrogenesis is accompanied by not only cellular renovation, but also metabolic stress. Therefore, macroautophagy/autophagy is postulated to be involved in this process. Previous reports have shown that suppression of autophagy during chondrogenesis causes mild growth retardation. However, the role of autophagy in chondrocyte differentiation still largely remains unclear. Here, we show the important role of autophagy on chondrogenesis. The transition of mesenchymal cells to chondrocytes was severely impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…As a ubiquitin activating enzyme, ATG7 plays an important role in autophagy formation and LC3 activation. Knocking out Atg7 in chondrocytes leads to growth retardation of chondrocytes, which is also related to the reduction of chondrocyte proliferation and the upregulation of apoptosis (Kang et al, 2017;Horigome et al, 2020).…”
Section: Key Molecules Involved In Autophagy and Oamentioning
confidence: 99%
“…As a ubiquitin activating enzyme, ATG7 plays an important role in autophagy formation and LC3 activation. Knocking out Atg7 in chondrocytes leads to growth retardation of chondrocytes, which is also related to the reduction of chondrocyte proliferation and the upregulation of apoptosis (Kang et al, 2017;Horigome et al, 2020).…”
Section: Key Molecules Involved In Autophagy and Oamentioning
confidence: 99%
“…We recently demonstrated that fibroblast growth factor (FGF) signaling, a critical regulator of skeletogenesis (Ornitz & Marie, 2015), activates autophagy in chondrocytes (Cinque et al, 2015). Moreover, chondrocytes that display defects in the autophagy pathway have altered ER morphology and function (Cinque et al, 2015;Bartolomeo et al, 2017;Kang et al, 2017;Horigome et al, 2019). These observations led us to hypothesize that ER-phagy in chondrocytes is regulated by the FGF signaling.…”
Section: Introductionmentioning
confidence: 99%
“…In that article, they mention that the lack of proteins such as Atg5, among others, reduces ex-vivo mineralization capacity. This effect has also been observed during chondrogenesis, where it has been reported that the suppression of autophagy would reduce the growth of proliferative chondrocytes, which would cause a severe growth retardation [ 66 ].…”
Section: Discussionmentioning
confidence: 81%